A portable cable head insulating rubber cap. Issue 4 (February 2020) - Zheng, Liwei; Li, Honglei; Liu, Mingjun; Guo, Jianling; Tian, Haoye; Sun, Dianlong
Abstract: The importance of safety, efficiency and economy in the production of power systems is increasing. However, in the daily work, the traditional insulating tape which is used to insulate the bare wires has the problems of low safety, poor efficiency and serious waste. To this end, a portable cable head insulating rubber cap is proposed. The advantages of the new insulating rubber cap are remarkable. It is easy to install and disassemble and can be reused. It effectively solves the problems of safety, efficiency and economy in the past working methods. It is of great significance to ensure safe production and improve the quality of work.